2017
DOI: 10.1080/21655979.2017.1313645
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of expanded and streamlined pipeline of PITCh knock-in – a web-based design tool for MMEJ-mediated gene knock-in, PITCh designer, and the variations of PITCh, PITCh-TG and PITCh-KIKO

Abstract: The emerging genome editing technology has enabled the creation of gene knock-in cells easily, efficiently, and rapidly, which has dramatically accelerated research in the field of mammalian functional genomics, including in humans. We recently developed a microhomology-mediated end-joining-based gene knock-in method, termed the PITCh system, and presented various examples of its application. Since the PITCh system only requires very short microhomologies (up to 40 bp) and single-guide RNA target sites on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…Nakamae et al [19] have been described as a newly advanced microhomology intermediated end assembly dependent gene knocks tool, named the PITCh tool, and offered numerous applications. Ventura et al [20] have described the probiogenomics as a new tool to get genetic perceptions into a variation of probiotic prokaryotes into the human guts.…”
Section: Global Perspective On Pharmaceuticals Bioengineered Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakamae et al [19] have been described as a newly advanced microhomology intermediated end assembly dependent gene knocks tool, named the PITCh tool, and offered numerous applications. Ventura et al [20] have described the probiogenomics as a new tool to get genetic perceptions into a variation of probiotic prokaryotes into the human guts.…”
Section: Global Perspective On Pharmaceuticals Bioengineered Toolsmentioning
confidence: 99%
“…Available bioengineered tools and techniques for the production of pharmaceuticals. [19] not only the appropriate micro homologies but also the primers to construct locus-specific donor vectors for PITCh knock-in. By using the newly established pipelines, a reporter cell line for monitoring endogenous gene expression, and transgenesis (TG) or knock-in/knockout (KIKO) cell line can be produced systematically [19].…”
Section: Unified Metabolic Database and Networkmentioning
confidence: 99%
“…2015; Sakuma et al . 2016; Nakamae et al . 2017), but there is still no success for targeted integration of large fragments over 20 kbp.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the detailed protocol, freely available materials, and online design tool for the CRISPR-mediated PITCh knock-in were provided by the authors Nakamae et al 2017). Along with these user-friendly resources, the application examples of CRISPR-mediated PITCh have become more diversified, e.g., high-throughput epitope tagging in cultured cells for chromatin immunoprecipitation (ChIP)-seq (Xiong et al 2017), the application in mammalian zygotes (Aida et al 2016;Nakagawa et al 2017), and in vivo somatic knock-in in mice (Yao et al 2017a) were reported one after another.…”
Section: Mmej/ssa-mediated Gene Knock-inmentioning
confidence: 99%